Making the most of what you pay for by delaying tasks to improve overall cloud instance performance - Sodré, Daniel Bougleux; Boeres, Cristina; Rebello, Vinod E. F. (Anais Estendidos do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2022)
Resource elasticity and server consolidation have long been among two of cloud computing’s most relevant management tools. Yet, exemplified with a scientific application use case, this paper highlights how judicious scheduling of tasks can help maximize resource utilization and improve performance and costs for both users and cloud providers. Developing an efficient cloud service for DNA sequence comparisons is adopted as a motivating use case. Using the bioinformatics tool MASA that finds an optimal pair-wise sequence alignment, we propose a model for co-scheduling multiple alignments on a single cloud instance. The resulting, practically optimal, non-preemptive schedule can effectively double the throughput of MASA-based sequence alignment workflows.